A Tuned Ether Electrolyte for Microporous Carbon-based Lithium–Sulfur Batteries Enabling Long Cycle Life and High Specific Capacity - TONOYA, Takeshi; ISHIKAWA, Masashi; MATSUI, Yukiko (Denki kagaku oyobi kōgyō butsuri kagaku, 2024)
Highly concentrated electrolytes have been studied to prevent the leaching diffusion of lithium (Li) polysulfides from sulfur (S) cathodes in Li–S batteries. Additionally, high-concentration electrolytes suppress the growth of Li dendrites at Li anodes. In this study, an ether-based high-concentration electrolyte was developed, enabling a microporous activated carbon–S composite cathode to achieve near-theoretical capacity performance and a long cycle life. The reference electrolyte was a high-concentration solution of Li bis(fluorosulfonyl)imide (LiFSI) in 1,2-dimethoxyethane (DME), known for its suitability for the stable dissolution and deposition of Li. However, its high viscosity impeded full penetration into the activated carbon–S composite cathode. To enhance the reversibility of the activated carbon–S composite cathode, we optimized the LiFSI-based electrolyte by adding hydrofluoroether (HFE) to reduce the viscosity and adjusting the LiFSI concentration to prevent the dissolution of Li polysulfides. Furthermore, the addition of Li difluoro(oxalate)borate (LiDFOB) to this electrolyte stabilized the cycling performance for over 100 cycles. When applied to a 1-Ah-class pouch cell, the electrolyte achieved an energy density of greater than 300 Wh kg−1.